A hairy tale: SIRT7 safeguards skin stem cells during aging. (16th August 2020) - Simon, Matthew; Emmrich, Stephan; Seluanov, Andrei; Gorbunova, Vera
Abstract : Stem cell regulation during both normal development and aging has become one of the fastest growing topics in biology. Here, new work by Li et al (2020) offers insight into the aging process within epithelial skin stem cells and highlights how SIRT7, a member of the sirtuin family of protein deacylases and mono‐ADP ribosylases, protects adult hair follicle stem cells from aging by ensuring their hair cycle progression. Abstract : Protein deacetylase SIRT7 supports maintenance of murine epithelial stem cells and hair regeneration.